2020
DOI: 10.1111/cpr.12803
|View full text |Cite
|
Sign up to set email alerts
|

Sensory nerve‐deficient microenvironment impairs tooth homeostasis by inducing apoptosis of dental pulp stem cells

Abstract: Objectives:The aim of this study is to investigate the role of sensory nerve in tooth homeostasis and its effect on mesenchymal stromal/stem cells (MSCs) in dental pulp. Materials and methods:We established the rat denervated incisor models to identify the morphological and histological changes of tooth. The groups were as follows:IANx (inferior alveolar nerve section), SCGx (superior cervical ganglion removal), IANx + SCGx and Sham group. The biological behaviour of dental pulp stromal/ stem cells (DPSCs) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The IANx surgery was modified with reference to previous studies (Hayano et al., 2018; Liu et al., 2020). Under deep anaesthesia, a skin extraoral horizontal incision was made to expose the masseter muscle.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The IANx surgery was modified with reference to previous studies (Hayano et al., 2018; Liu et al., 2020). Under deep anaesthesia, a skin extraoral horizontal incision was made to expose the masseter muscle.…”
Section: Methodsmentioning
confidence: 99%
“…Type H vessels have been identified as a specialized bone-specific vessel type that promotes bone healing (Zhang et al, 2020). However, there have been few studies on the involvement of type H vessels in reparative dentine formation.…”
Section: Dental Nerve Sprouting Precedes Angiogenesis At Sites Of Rep...mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, the inferior alveolar nerve tube is often injured due to trauma or surgery, significantly impairing patients' quality of life. Thus, the use of DPSCs as seed cells to heal the inferior maxillary nerve/inferior alveolar nerve damage is an area that warrants further investigation [84]. Figure 1 below describes the mechanism of DPSCs protection on neural.…”
Section: Nerve Repairmentioning
confidence: 99%
“…Moreover, changes in pulpal innervation may be partly responsible for degenerative alterations in rodent teeth. Several studies have reported that denervated incisors exhibit reduced microhardness and turn chalky about 1 week after operation and fracture 1 month after denervation (Krage et al 2005, Zhao et al 2014, Hayano et al 2018, Liu et al 2020.…”
Section: Effects On Healing In Pulpitismentioning
confidence: 99%